Na drogach człowieczeństwa — filozofia Henryka Elzenberga - Cieciera, Elżbieta (Folia Philosophica, 2018)
The paper aims at grasping Henryk Elzenberg’s thought on human condition on both social and universal level. By showing an individual in the world doomed to relations Elzenberg tries to analyse distortion and over-interpretations of impulses coming both from human psyche and from civilization. By stigmatization of the shallowness of life and omnipresent utilitarianism he wants to find an alternative to raise the man to higher level, to salvation. For this he proposes focusing on perfect values, independent from man. Noticing the difference between the nature of human and other creatures he highlights the role discovering one’s personal capacities and the necessity of gathering them in what is called culture. Setting as the demand the turn first in mind, related to deepening of self-consciousness, and then also spiritual, he sets alternative roads of experiencing the world, both that given in senses and alternative-one. All of his ideas are ways of building humanity to be more essential and rewarding.